Competência profissional do enfermeiro de urgência e emergência: desenvolvimento do processo de avaliação - Holanda, Flavia Lilalva de [UNIFESP] (2016)
Objectives: To develop a process to create an instrument to evaluate the professional competencies of nurses in emergencies and to evaluate the evidence of validity and internal consistency of the proposed competencies. Method: Quantitative study with a non-experimental, descriptive and methodological design, carried out from 2011 to 2016, in a public university in the city of São Paulo, Brazil, based on the psychometric benchmark. In order to meet the criteria of the types of research and the use of this reference in the elaboration of an instrument to measure human behavior, the study was developed in stages, according to Pasquali. These steps were carried out in different and consecutive ways in the necessary Theorical, Empirical and Analytical Procedures to direct the investigation to its final objective. As for the theorists, the objective was to base the construction to scientifically support the instrument to be elaborated with necessary actions to the competent practice of the nurse in emergencies. It was dedicated to the survey of the literature and to the Construction of a Professional Competency Matrix of the nurse in emergency services. In this construction, it is considered empirical to evidence already obtained knowledge and experience of the researchers to establish the quantitative and nominal aspects, as well as the constitutive and operational definitions of the process. The Matrix was composed of Basic and Associated Competences and from it a Professional competency profile of nurses working in emergency services was proposed, aligned with the market trends, the particularities of Nursing in emergencies, the existing studies and the opinion of experts who considered the ownership of the actions to the performance Nurses in this area necessary for the definition of the construct. The Competence Assessment Instrument was organized into five parts: a spreadsheet with measurable actions at five levels of competence; Scale of evaluation of the degree of professional competence of nurses in emergencies; Personal and professional characterization data of the research subject and three fictitious cases. In Empirics, the sample, the application of the pilot instrument and the data collection were calculated and defined, and the psychometric quality of the instrument was evaluated. The Analytics were descriptive and inferential. Results: From the eight Basic Competences and the 32 Associated Competencies indicated in the Matrix, there were 56 attitudes / behaviors represented by actions named Identifying Issues generating the Competence Profile. After verifying the evidence of validity based on the content of the Identification Questions by nurse experts in the subject, we searched for evidence of validity of the item of the construct proposed in the instrument. 448 nurses participated in this process, with 407 self-assessments and 41 managers responding to 407 hetero-evaluations, making a total of 814 instruments applied in hospitals, Emergency Care Units 24h (AMA) and Mobile Medical Emergency Services (SAMU). The exploratory factorial analysis of the 81 items indicated the existence of seven factors that, after excluding three of these items, explained 66.5% of the total data variance. Alpha Cronbach ranged from 0.79 to 0.98. The evaluation of the scores by characteristics verified different means by gender, institutions, specialists and nurses with different courses inherent in emergencies. Conclusion: A process was developed for the creation of an Instrument for the Evaluation of Professional Competences of nurses in emergencies with evaluation of validity evidences throughout the study.